Security Ontology OntoSecRPA for Robotic Process Automation Domain - Anastasiya Kurylets; Nikolaj Goranin (Applied Sciences, 2023)
Robotic process automation (RPA)* based on the use of software robots has proven to be one of the most demanded technologies to emerge in recent years used for automating daily IT routines in many sectors, such as banking and finance. As with any new technology, RPA has a number of potential cyber security weaknesses, caused either by fundamental logical mistakes in the approach or by cyber-human mistakes made during the implementation, configuration, and operation phases. It is important to have an extensive understanding of the related risks before RPA integration into enterprise IT infrastructure. The main asset operated by RPA is confidential enterprise data. Data leakage and theft are the two main threats. The wide application of RPA technology in information security-sensitive sectors makes the protection of RPA against cyber-attacks an important task. Still, this topic is not yet adequately investigated in the scientific press and existing articles mainly concentrate on stating the RPA security importance and describing some threats. In this article, we present a flexible tool, security-oriented ontology OntoSecRPA*, which systematically describes RPA-specific assets, risks, security, threats, vulnerabilities, and countermeasures. To the best of our knowledge, there are currently no ontologies available that are specific to the RPA domain, and existing security ontologies lack RPA-related features. In the future, the proposed ontology can be updated and used in different ways, for example, as a checklist for risk management tasks in RPA solutions and a source of information for an expert system or a concentrated domain-specific source of information, which indicates its wide practical application. The proposed ontology was formally verified by applying ontology completeness assessment and used for risk assessment in a sample scenario.